Game Based Learning Using Construct for Basic English Vocabulary at Elementary School Students - Akmal Perdana; Auzil Mustaqim Herman; Fiqih Hana Saputri; Eka Uliyanti Putri Br Bangun (Universitas Islam Raden Rahmat, Malang, 2025)
English basic vocabulary learning plays a very important role for elementary school students, as it serves as the main foundation in mastering language skills, including reading, writing, listening, and speaking. Thus, this research is focused on development. Basic English Vocabulary Education Based on Construct, which is an interactive learning method utilizing digital technology of educational games to increase the effectiveness for learning. Construct, as a platform for developing educational games for students can understand basic English vocabulary in a more enjoyable and non-monotonous way. This study applies the Multimedia Development Life Cycle (MDLC) method with a constructivist approach, which allows students not only to receive information passively but also to actively build their understanding through exploration, experimentation, and direct interaction with various elements in educational games. Based on the feasibility assessment results, the satisfaction level of respondents obtained from the questionnaire reached 93% out of a total of 10 respondents. The construct based educational game is an effective tool for improving students' grasp of basic English vocabulary through educational game-based learning.